Numerical study and optimisation of the boiling of refrigerant in a vertical corrugated tube using vapour phase tracking - Mesgarpour, Mehrdad; Alizadeh, Rasool; Mahian, Omid; Dalkilic, Ahmet Selim; Ahn, Ho Seon; Wongwises, Somchai (PERGAMON-ELSEVIER SCIENCE LTD, 2022)
The present study deals with the numerical modelling of the boiling of a refrigerant flowing downward in a vertical corrugated tube while hot water is flowing upward inside an outer tube. Considering the R-134a refrigerant, we employ optimisation and vapour phase tracking methods in an attempt to improve the heat transfer during the boiling process. The two-phase flow is simulated by a novel approach in which the changes in the vapour-liquid interface are tracked at each time step. Differential evolution is used to optimise the shape of the corrugations on the surface of the tube so as to achieve maximum heat transfer and minimum friction. Through this structural optimisation, the heat transfer rate can be enhanced by 11%, while the friction factor decreases by 9%. Furthermore, the findings show that, as the corrugation depth is varied, the average vapour quality increases slightly before suddenly decreasing. According to our findings, the Nusselt number can be increased by up to 12%. Furthermore, the results show that optimisation improves the average vapour quality by more than 10%. (c) 2021 Elsevier Ltd. All rights reserved.
Keywords: EVAPORATION HEAT-TRANSFER; LEVEL SET METHOD; PRESSURE-DROP; DIFFERENTIAL EVOLUTION; THERMAL-CONDUCTIVITY; FLOW; CONDENSATION; R-134A; SIMULATIONS; PREDICTION; Thermodynamics; Engineering; Mechanics